DEVELOPING GARTIC.IO ON PAST TENSES TO TEACH STUDENTS VOCABULARY OF 8TH B CLASS SMPN 5 BLITAR: English - Muhammad Eko; Istina Atul Makrifah; Siti Rofi’ah (Prodi Tadris Bahasa Inggris, 2023)
This research is to determine the processes and the results of developing Gartic.io on past tenses to teach students vocabulary in the 8th B Class of SMPN 5 BLITAR. Learning language is one of the many things that students learn in school. English is one of the languages students learn at school, in the learning processes one of the most effective ways to support student learning is through the use of media. Research and Development (R&D) employing the ADDIE model used by researcher in this study. Observation, interview, and questionnaire used to collect data from students. 82.5% on instrument validation which is considered “valid”, 87.5% on material expert validation which is considered “very valid”, and 77.5% on media expert validation which is considered “valid”. Second questionnaire for getting the students’ responses about the media obtain 74% which is considered “valid”.